The impact of a humanized bile acid composition on atherosclerosis development in hypercholesterolaemic Cyp2c70 knockout mice - Tess Yntema; Tim R. Eijgenraam; Niels J. Kloosterhuis; Rick Havinga; Mirjam H. Koster; Milaine V. Hovingh; Jan Freark de Boer; Debby P. Y. Koonen; Folkert Kuipers (Scientific Reports)
Abstract Bile acids (BAs) play important roles in the context of lipid homeostasis and inflammation. Based on extensive preclinical mouse studies, BA signaling pathways have been implicated as therapeutic targets for cardiovascular diseases. However, differences in BA metabolism between mice and humans hamper translation of preclinical outcomes. Recently, we generated Cyp2c70 −/− mice with a human-like BA composition lacking mouse/rat specific muricholic acids. We employed this model to assess the consequences of a human-like BA pool on atherosclerosis and heart function in hypercholesterolaemic mice. We overexpressed a PCSK9 gain-of-function (GOF) mutation in the liver of male Cyp2c70 −/− and Cyp2c70 +/− control mice, and fed these mice a Western-type diet (WD) for 12 weeks. Cyp2c70 −/− mice displayed a hydrophobic BA pool rich in chenodeoxycholic acid. Cyp2c70 −/− mice showed reduced hepatic total cholesterol and triglycerides (p < 0.05) combined with lower plasma total cholesterol (p < 0.05) and triglycerides (p = 0.05) due to lower VLDL levels. Circulating white blood cells remained largely unaffected in Cyp2c70 −/− mice. Interestingly, we found a trend (p = 0.08) towards smaller atherosclerotic lesions in the aortic root of Cyp2c70 −/− mice, but no effect on cardiac morphology or function was observed. To conclude, a human-like BA composition ameliorated PCSK9-GOF-induced hypercholesterolaemia in WD-fed mice which translated into a tendency towards smaller atherosclerotic lesions.